Letter from Carl D. Duncan to Patricia Whiting, January 31, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan provides a poem he wrote inspired by the reading of "My Fair Lady". He also outlines varied travel plans dependent on the weather.